Factors Related To The Compliance In The Use Of Personal Protective Equipment At Production Employees At Pt Indofood Cbp Sukses Makmur Noodle Division, Pekanbaru - Yuli Devila; Santoso; Herniwanti; Endang Purnawati Rahayu; Kamali Zaman (Science Midwifery, 2022)
The use of PPE is one of the problems in the world of work. This can increase the level of risk of loss, both material and non-material. In general, companies have implemented an OHS management system, in which there are also provisions for the use of Personal Protective Equipment (PPE). However, in reality PPE is not always worn when working, many workers are found who do not use PPE. Compliance with the use of personal protective equipment is a person's attitude in following the rules set by the organization to protect part or all of the body from the dangers of work-related accidents and diseases. Based on the initial survey, it was found that there were 17 employees who did not comply with using personal protective equipment. The purpose of this study was to analyze factors related to Compliance with the Use of Personal Protective Equipment for employees in the production section at PT Indofood CBP Sukses Makmur TBK Noodle Division Pekanbaru. The method in this study used a quantitative approach with a Case Control research design with a total a sample of 34 people. The research was conducted from August to September 2021. Data collection was carried out using a questionnaire using the Google form. Data analysis was carried out using univariate, bivariate and multivariate. The analysis technique used is multiple logistic regression using the SPSS program. Based on the results of the study there is a significant relationship between attitude variables, availability of personal protective equipment, supervision, age and years of service with adherence to the use of personal protective equipment. The most dominant factor in this research is attitude. Suggestions for PT Indofood CBC Sukses Makmur are to form regulations, carry out strict inspections and sanctions for employees who are not disciplined in using personal protective equipment, and provide rewards for employees who comply in using personal protective equipment (PPE).